2022
DOI: 10.3390/w14030346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Light/Dark Cycle and Concentration of Tannery Wastewater in the Production of Biomass and Metabolites of Industrial Interest from Microalgae and Cyanobacteria

Abstract: The tanning industry transforms animal skins into leather and produces liquid effluents with a high organic and inorganic pollutant load. This work evaluated the effect of the tannery wastewater (TWW) concentration and the light/dark cycle on the production of biomass, carbohydrates, proteins, lipids, and pigments (carotenoids and phycobiliproteins) on two microalgae (Chlorella sp. and Scenedesmus sp.) and one cyanobacterium (Hapalosiphon sp.). A non-factorial central experimental design with a response surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…COD, the removal of pollutants, depends on the amount of OH available for oxidation; therefore, the generation of OH is crucial, and this process is affected by the pH of the wastewater. As observed in this work, an acidic pH favors the generation of OH and its reaction with the oxidation of the pollutant load, while high pH values decrease the COD removal rate; studies have shown that at high pH (9)(10)(11)(12) the dissociated form of hydrogen peroxide acts as a scavenger of the generated OH*, which affects the reduction of COD removal due to the loss of carbon oxidation potential [20,30]. Temperature affects the rate of peroxide degradation, the generation of hydroxyl radicals, and the solubility of the target impurity, among other factors that contribute to the effectiveness of the UV/H 2 O 2 oxidation process.…”
Section: Codsupporting
confidence: 63%
See 1 more Smart Citation
“…COD, the removal of pollutants, depends on the amount of OH available for oxidation; therefore, the generation of OH is crucial, and this process is affected by the pH of the wastewater. As observed in this work, an acidic pH favors the generation of OH and its reaction with the oxidation of the pollutant load, while high pH values decrease the COD removal rate; studies have shown that at high pH (9)(10)(11)(12) the dissociated form of hydrogen peroxide acts as a scavenger of the generated OH*, which affects the reduction of COD removal due to the loss of carbon oxidation potential [20,30]. Temperature affects the rate of peroxide degradation, the generation of hydroxyl radicals, and the solubility of the target impurity, among other factors that contribute to the effectiveness of the UV/H 2 O 2 oxidation process.…”
Section: Codsupporting
confidence: 63%
“…The use of micro-organisms to biodegrade organic matter in tannery wastewater has been reported; studies of these processes have used biological agents, including bacteria, microalgae, and some fungi. Batch reactor (SBR) systems have been used to treat tannery wastewater, reducing concentrations of COD and BOD by 70-88% [8,9]. Activated sludge systems show exciting results in BOD 5 and COD removal of 90% and 80%, respectively, with specific suspended solids in the mixed liquor (MLVSS) operating requirements of 3500 mg/L while maintaining an aeration time of 12 h [10].…”
Section: Introductionmentioning
confidence: 99%
“…Both algae were grown in liquid bold basal medium, while the cyanobacteria were grown in liquid BG-11 medium. Every strain was grown in 1 L GL-45 flask with 600 mL of culture media under a 12-12 h photoperiod, 110 µmol m −2 s −1 , mixed with filtered air enriched with 1% (v/v) of CO 2 at a flow of 0.6 vvm and 25 ± 2 • C [33].…”
Section: Microorganismsmentioning
confidence: 99%
“…For each experiment, a 500 mL GL-45 flask with 250 mL of working volume was used (25 mL of algae plus 225 mL of wastewater). Each flask was grown for 20 days under 200 µmol m −2 s −1 , 25 ± 2 • C and mixed using filtered air enriched with 1% (v/v) of CO 2 [33]. The wastewater concentrations and the light/dark cycles were adjusted according to the experimental design.…”
Section: Biomass Concentration and Nutrient Removalmentioning
confidence: 99%
“…For this, it is known that photosynthetic metabolism allows an accumulation of energy during the supply of light, thus ensuring that the process can be continued for some time in the absence of light. In this line of work, the most used cycles are between 24 h:0 h and 12 h:12 h light:dark, and they can be divided into two or more cycles per day or in a proportion of seconds or milliseconds [ 16 ]. Thus, knowing the factors that determine the biomass productivity and the biochemical behavior in the profile of microalgae in the face of the different cultivation conditions, it is possible to elucidate more efficient strategies and optimize scaling for productions that cover the current global needs for food.…”
Section: Introductionmentioning
confidence: 99%